Lost in care pathway: a qualitative investigation on the health system delay of extra pulmonary tuberculosis patients in Bangladesh - Sarker, Malabika; Mohammad, Din; Paul, Sukanta; Akter, Rahima; Islam, Shayla; Biswas, Goutam; Hossain, Asheque; Islam, Akramul (BRAC Univeristy, 2018)
This article was published in the BMC Infectious Diseases [© 2017 BMC Infectious Diseases] and the definite version is available at : https://doi.org/10.1186/s12913-017-2181-8 . The Journal's website is at: https://bmchealthservres.biomedcentral.com/articles/10.1186/s12913-017-2181-8